قانون المخالفة الصوتية وأثره في نمو الثروة اللفظية للعربية الفصحى - بحرة سامر (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
"ليس في العربية الفصحى جذورٌ رباعيةٌ أصيلةٌ، وقدرٌ كبيرٌ من الكلمات الرباعيّة إنما اشتُقّ من أصولٍ ثلاثيّة بطريق المخالفة الصوتية". إنها الفرضية التي انطلق منها هذا البحث معتمدا في روزها على مدوّنة مؤلفة مما يربو على ألفين وثمانيمائة جذرٍ رباعيٍّ جمعها الباحث من متن واحدٍ من أضخم معاجم العربية هو "لسان العرب". والكلمة الرباعية، موضوع هذا البحث،هي تلك المؤلفة من أربعة صوامت، فيدخل في ذلك ما كان منها مجرداً "فعلل" وما زيد فيه سابقة تصريفية " تفعلل" سواء أكان أصلياً أم ملحقاً بالأصليّ "فوعل، فنعل ، تفيعل..." سواءٌ اختلفت صوامته بعضها عن بعض أم تكرر شيءٌ منها. ولئن سعى البحث إلى تبني مقولات اللسانيات الحديثة ومصطلحاتها، لقد ظل متسلحاً بالتراث اللغوي، يسترفده فيرفده، عارضاً تلك المقولات على صفحات عقول العرب من علماء اللغة، عاقداً معهم جدالاً علمياً يتجاوز حدود الزمن غير متحرجٍ من توجيه النقد المقوّم لبعض آرائهم، نقدٍ يهدف إلى سدّ خللٍ من طرف، والتنبيه على سبق العرب في مضمار البحث اللغوي وفضلهم على غيرهم من الأمم فيه من طرفٍ آخر. As one of metaplasma in languages, dissimilation has played a highly significant role in changing the modes of words in standard Arabic, which have enlarged the Arabic dictionary throughout the ages. This research aims at detecting the influence of dissimilation in deriving the quadrilateral words out of trilateral geminated words, depending on a data consisting of more than 2800 quadrilateral roots, collected by the researcher from one of the largest Arabic dictionaries: Lisan Al-Arab. Through this research, which adopts a recent linguistic concept, the researcher wants to establish contact with the Arabic linguistic heritage. By doing so, he seeks the ancient linguists’ attitudes toward the modem linguistic concept, which, in turn, helped to interpret the way many quadrilateral words are derived by the dissimilation. That contact, however, has been based on a scientific objective argument and constructive criticism of the ancient viewpoints, which violate objective science. On the other hand, this research gives the credit to the ancient scholars for their outstanding attempts on etymologizing the quadrilaterals.